Pengembangan Wakaf, Infak, dan Sedekah Sebagai Upaya Pengentasan Kemiskinan: Studi Kasus Masyarakat Muslim Surabaya - Machmudah, Ella Lailatul; Faiz An Nashrullah; Wigati, Sri (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
Abstract: This research discusses the efforts to develop the non-zakah Islamic economy, namely waqf, infaq, and sadaqah, to empower and strengthen the Islamic economy. This paper seeks to understand the issue of poverty in Surabaya's Muslim community. Based on the data obtained from the official website of the Surabaya government, the poverty rate in Surabaya has been unstable in recent years. However, the poverty rate in Surabaya is closer to a significant decline; this cannot be separated from the government's efforts to alleviate poverty through certain policies. Islam views poverty as a form of test that Allah SWT gives, even though it is not considered a pleasure. Linking this description with Yusuf Qordhowi's ideas about the concept of poverty alleviation, one of which is the presence of baitul mal (management of state assets whose distribution is beneficial for the benefit of the people), and the existence of voluntary alms and infaq.Keywords: Poverty Alleviation, Infaq Waqf, and Alms, Islamic Economics